Computer modeling of the gas discharge in the electrodeless lamp - Frolova, T.I.; Churyumov, G.I. (Вопросы атомной науки и техники, 2015)
The paper is devoted to computer modeling of gas discharge processes underlying working electrodeless light sources. Researches carried out for the analysis of the relationship of the radiation spectrum to the microwave lamps from the pressure in the bulb and the concentration of the substance which revealed that, when using the LTE model in the description of the plasma discharge, various pressure influence the spectral characteristics of the electrodeless lamps.